Seminar Transformasi Sinergi Staf Pelaksana Perpustakaan UTM 2019 13-14 November 2019, Perpustakaan UTM (Bangunan PRZS), Johor Bahru, Johor - Seminar Transformasi Sinergi Staf Pelaksana Perpustakaan UTM (2019 : Johor Bahru); Farhan Yuskelana, contributor; Azharuddin Azmi, contributor; Habibah Samsudin, contributor; Norhayati Ab. Majid, contributor; Nurfarahin Jasmine See Abdullah, contributor; Salihuddin Bakhri, contributor; Hamsapinah Hamdan, contributor; Siti Atiqah Norsalim, contributor; Nor Shaliza Mohd Basarudin, contributor; Suraya Jaapa, contributor; Akmal Alif Amran, contributor; et al. (Johor Bahru, Johor : Perpustakaan UTM, 2019)
Includes bibliographical references and indexes.